SEMIOTIC ANALYSIS OF THE AGA ROSÉ LABEL FROM HATTEN WINES BASED ON ROLAND BARTHES' THEORY - Hanindharputri, Made Arini; Artayasa, I Nyoman; Remawa, Anak Agung Gede Rai; Dewi, Alit Kumala (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
This study examines the semiotic meanings in the label design of Aga Rosé, a wine product by Hatten Wines, through Roland Barthes' semiotic theory. It focuses on how the label's visual elements communicate cultural and branding messages. The purpose of this study is to explore the denotative and connotative meanings of the Aga Rosé wine label and how these elements contribute to brand image formation and consumer perception. This research employs a qualitative methodology, analyzing visual elements such as color, imagery, and text, which represent local cultural values, based on Roland Barthes' semiotic approach. The Aga Rosé label effectively incorporates cultural symbols and aesthetics, reflecting Indonesian cultural identity. This design strengthens consumers' emotional attachment to the brand and enhances loyalty. The findings underscore the importance of culturally inspired design as a strategy for building strong brand identities in competitive markets.